Development of short and highly potent self‐assembling elastin‐derived pentapeptide repeats containing aromatic amino acid residues. (10th December 2015) - Taniguchi, Suguru; Watanabe, Noriko; Nose, Takeru; Maeda, Iori
Abstract : Tropoelastin is the primary component of elastin, which forms the elastic fibers that make up connective tissues. The hydrophobic domains of tropoelastin are thought to mediate the self‐assembly of elastin into fibers, and the temperature‐mediated self‐assembly (coacervation) of one such repetitive peptide sequence (VPGVG) has been utilized in various bio‐applications. To elucidate a mechanism for coacervation activity enhancement and to develop more potent coacervatable elastin‐derived peptides, we synthesized two series of peptide analogs containing an aromatic amino acid, Trp or Tyr, in addition to Phe‐containing analogs and tested their functional characteristics. Thus, position 1 of the hydrophobic pentapeptide repeat of elastin (X 1 P 2 G 3 V 4 G 5 ) was substituted by Trp or Tyr. Eventually, we acquired a novel, short Trp‐containing elastin‐derived peptide analog (WPGVG)3 with potent coacervation ability. From the results obtained during this process, we determined the importance of aromaticity and hydrophobicity for the coacervation potency of elastin‐derived peptide analogs. Generally, however, the production of long‐chain synthetic polypeptides in quantities sufficient for commercial use remain cost‐prohibitive. Therefore, the identification of (WPGVG)3, which is a 15‐mer short peptide consisting simply of five natural amino acids and shows temperature‐dependent self‐assembly activity, might serve as a foundation for the development of various kinds of biomaterials. Copyright © 2015 European Peptide Society and John Wiley & Sons, Ltd. Abstract : A novel, short Trp‐containing elastin‐derived peptide analog, (WPGVG)3, with potent coacervation ability was identified through a screening process, which demonstrated the importance of aromaticity and hydrophobicity for the coacervation potency of elastin‐derived peptide analogs. The identified (WPGVG)3 peptide, which is a 15‐mer short peptide comprising simply five natural amino acids, shows temperature‐dependent self‐assembly activity and might provide a foundation for the development of various kinds of biomaterials.